Two-level inter-area oscillation dampers design by monte carlo simulation - Ngamroo, Issarachai (My University, 2019)
Various system operations such as load changes, time delays, communication failure, and line outages have an influence on the stabilizing effect of inter-area damping controllers. Moreover, the penetration of large wind farms makes power oscillations problem more complicated. This paper proposes the two-level control design of power system stabilizers and power oscillation dampers of wind turbines with doubly fed induction generator by Monte Carlo simulation (MCS) and probability. In the twolevel damping control, the centralized damper acts as the main control while the local damper works as the backup control when the communication failure occurs. Using the MCS to produce random operating points, the parameters tuning of centralized and local dampers is independently performed by the particle swarm optimization so that the probability of expected damping ratio is maximized. Study results in the modified IEEE New England 39 bus system guarantee the damping effect and robustness of the proposed control.
Keywords: Doubly-fed induction generator (DFIG); Inter-area oscillation; Monte Carlo simulation (MCS); Power system stabilizer; Probability; Wind turbine (WT)